Gastrointestinal peptides and food intake regulation - Bloom, Stephen (Henry Stewart Talks, 2009)
Anti-obesity agents, Bariatric surgery, The gut hormones, Ghrelin, Energy intake free-choice meal, Meal intake after Ghrelin infusion, Why do you feel less hungry after a meal?, Three types of satiety action, Peptide YY (PYY), GI tract distribution of PYY, Post-prandial secretion of PYY, Effect of PYY on food intake, Glucagon-like peptide 1, The effect of chronic GLP-1 on body weight, Oxyntomodulin, Leptin change, Human pancreatic polypeptide, Peptides as drugs: better targeted
Archived at 2015/11/30